The effect of high approach-motivated positive affect on selective attention under high perceptual load - Liu, Fang; Zhang, Qin (Frontiers in Human Neuroscience, 2025)
IntroductionSelective attention is a crucial mechanism that enables humans to navigate complex environments and accomplish targeted tasks, garnering significant interest from researchers. Numerous studies have found that selective attention can be influenced by emotions; however, previous research has primarily focused on the effects of valence and arousal, neglecting the role of motivation, another dimension of emotion. Additionally, it remains unclear whether emotional motivation’s influence on selective attention differs across various levels of perceptual load.MethodsThis study employed a modified perceptual load Flanker task, using behavioral measures and event-related potentials (ERPs) technique to investigate how the intensity of approach-motivated positive affect influences selective attention under different levels of perceptual load. In each trial, participants were first shown pictures of food or scenes to induce high or low approach-motivated positive affect, followed by a modified perceptual load Flanker task where a searchable array of letters was arranged in a virtual circle around a central fixation point, with an interference letter presented on either the left or right periphery. The searchable array included one target letter and either five identical (low perceptual load) or different irrelevant letters (high perceptual load). Participants were required to identify the target letter and respond with a button press.ResultsThe findings revealed that under conditions of high perceptual load, participants with low approach-motivated positive affect exhibited slower reaction times than those with high approach-motivated positive affect. Meanwhile, the ERP results indicated that under high perceptual load, low approach-motivated positive affect induced a greater N1 in the parieto-occipital region compared to high approach-motivated positive affect. Additionally, high approach-motivated positive affect evoked a greater N2 in the frontal region and a smaller P3 in the parietal region compared to low approach-motivated positive affect and neutral affect.DiscussionThese results demonstrate the inhibitory effect of low approach-motivated positive affect and the enhancing effect of high approach-motivated positive affect on performance in the high perceptual load Flanker task.